2014
DOI: 10.1038/ncomms5513
|View full text |Cite
|
Sign up to set email alerts
|

NEDD4 ubiquitinates TRAF3 to promote CD40-mediated AKT activation

Abstract: CD40, a member of tumour necrosis factor receptor (TNFR) superfamily, has a pivotal role in B-cell-mediated immunity through various effector pathways including AKT kinase, but the signal transduction of CD40-meidated AKT activation is poorly understood. Here we report that the neural precursor cell expressed developmentally downregulated protein 4 (NEDD4), homologous to E6-AP Carboxyl Terminus family E3 ubiquitin ligase, is a novel component of the CD40 signalling complex. It has a key role in CD40-mediated A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…The conventional IPs were performed as previously described [10][11][12][13]. The denaturation IPs for detection of ubiquitination were performed according to the study by Fang, et al [14] with slight modifications, briefly, lysates from Bel-7402 cells under different treatment were prepared in Western/IP lysis buffer (Beyotime, Haimen, China). SDS was added into the supernatants of cell lysates to a final concentration 1%, noncovalently associated proteins were removed by boiling at 100°C for 10 min.…”
Section: Immunohistochemistry (Ihc) Immunefluorescence (If) and Wesmentioning
confidence: 99%
“…The conventional IPs were performed as previously described [10][11][12][13]. The denaturation IPs for detection of ubiquitination were performed according to the study by Fang, et al [14] with slight modifications, briefly, lysates from Bel-7402 cells under different treatment were prepared in Western/IP lysis buffer (Beyotime, Haimen, China). SDS was added into the supernatants of cell lysates to a final concentration 1%, noncovalently associated proteins were removed by boiling at 100°C for 10 min.…”
Section: Immunohistochemistry (Ihc) Immunefluorescence (If) and Wesmentioning
confidence: 99%
“…Proteins in the conditioned medium (5 ml) were concentrated by TCA precipitation. Concentrated protein samples were analyzed by SDS-PAGE and in-gel digestions were carried out as previously described [38]. The digested samples were analyzed by nanoLC-MS/MS (nanoACQUITY UPLC and SYNAPT G2 HD mass spectrometer; Waters).…”
Section: Mass Spectrometry Analysismentioning
confidence: 99%
“…Mice deficient in Nedd4 (Nedd4 −/− mice) were neonatal lethal, with delayed embryonic development and reduced growth and body weight due 20 . It has been found that Nedd4 plays an important role in immune cells including T cells 21 and B cells 22 , however, the physiological functions and molecular mechanism of Nedd4 in macrophages still need to be investigated.…”
Section: Introductionmentioning
confidence: 99%